Biocatalytic Depletion of Tumorigenic Energy Sources Driven by Cascade Reactions for Efficient Antitumor Therapy. Issue 42 (12th September 2022) - Xiao, Ya‐Ping; Chen, Peng‐Hang; Lei, Shan; Bai, Fang; Fu, Lian‐Hua; Lin, Jing; Huang, Peng
Abstract: Glucose and lactate play important roles for tumor growth. How to simultaneously deprive tumors of glucose and lactate is a big challenge. We have developed a cascade catalytic system (denoted as FPGLC) based on fluorinated polymer (FP) with co‐loading of glucose oxidase (GOx), lactate oxidase (LOx), and catalase (CAT). GOx and LOx deprive glucose and lactate, respectively, resulting in abundant hydrogen peroxide (H2 O2 ) generation. Meanwhile, CAT catalyzes H2 O2 into O2, which not only promotes catalytic reactions of GOx and LOx for consuming more glucose and lactate, but also alleviates tumor hypoxia. Benefiting from the excellent cross‐membrane and transmucosal penetration capacities of FP, FPGLC rapidly accumulated in tumors and subsequently mediated enhanced cascade catalytic therapy under the guidance of photoacoustic imaging. These results demonstrate that the dual depletion of glucose and lactate with O2 supply is a promising strategy for efficient antitumor starvation therapy. Abstract : A cascade catalytic system based on the co‐delivery of glucose oxidase (GOx), lactate oxidase (LOx), and catalase (CAT) using a fluorinated polymer was developed for efficient antitumor starvation therapy through simultaneous glucose/lactate depletion under continuous O2 supply and guided by photoacoustic imaging.